De la compétence de service aux compétences de coordination et d’orchestration : Autour du conseiller funéraire - Sandrine Caroly; Pascale Trompette (Perspectives Interdisciplinaires sur le Travail et la Santé)
In describing the funeral director, who is the symbol of funeral services, we gain access to the main skill registries of funeral operators during the entire provision of services, which include: the handling of the deceased, the public service, and the funeral ritual. As the individual who manages the funeral, the funeral director historically is a person with variable geometry, evolving from a public persona within the local community’s important religious networks to that of a technical and commercial consultant, but increasingly invested with the role of "officiant" in the production of funerals as cultural and symbolic property. This article is interested in how the funeral director’s skills are applied through three main skill registries: management of the interaction with the client, interprofessional coordination, and finally the "orchestration" of the event and the sacred aspect in conducting the funeral operations. Analysis of the funeral activity revealed essential characteristics of service competencies.